উম্মুল মুমিনীন উম্মু সালামা রা. ও তাঁর ফিকহী অভিমত : একটি পর্যালোচনা |Ummul Muminin Ummu Salama R. and Her Juristic Opinions: An Analysis (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
From among the wives of the prophet pbuh Ummu Salamah R was also renowned as Aisha for her intellectual contributionl. In terms of recording prophetic biography and Sunnatic knowledge, she was just next to Aishah R. Being widow with her three children Ummu Salama had been married to the messenger of Allah when she was 29. For her intellectual and political wisdom, Ummu Salama had secured an important place from among the other wives of the prophet pbuh and was the last to pass away. She was very meritorious and meticulous and narrated 378 hadiths from Muhammad pbuh. In addition, she had exposed jurisprudential expertise in fiqh (juridical issues). This article endeavours to discuss her fiqh teaching method and mention her juridical opinions as she had viewed in different legal problems. By employing descriptive method, thus this article aims to demonstrate how she looked into juridical issue related hadiths and extracted legal opinions therefrom and thereby manifest the deeper intellectualism of Ummu Salama R in fiqh rulings especially that of woman studies.সারসংক্ষেপ : উম্মু সালামা রা. রাসূল স.-এর স্ত্রীদের মধ্যে প্রখর মেধা দিয়ে সীরাত ও হাদীস চর্চায় আয়েশা রা.-এর পরই অত্যন্ত গুরুতপূর্ণ স্থানে স্থলাভিষিক্ত। তিনি বিধবা অবস্থায় ২৯ বছর বয়সে ৩ সন্তানসহ রাসূল স.-এর সাথে বিবাহ বন্ধনে আবদ্ধ হন এবং তাঁর বুদ্ধিমত্তা ও রাজনৈতিক প্রজ্ঞার দ্বারা রাসূল স.-এর অন্যান্য সহধর্মিনীদের মধ্যে উন্নত মর্যাদার অধিকারিণী হন এবং তাঁদের মধ্যে সর্বশেষ দুনিয়া থেকে বিদায় নেন। তিনি প্রখর স্মৃতিশক্তির অধিকারিণী ছিলেন এবং রাসূল স. থেকে ৩৭৮টি হাদীস বর্ণনা করেন। হাদীস বর্ণনার পাশাপাশি তিনি ফিক্হশাস্ত্রেও বুৎপত্তি অর্জন করেন। অত্র প্রবন্ধে তাঁর ফিকহ শিক্ষা ও শিক্ষাপ্রদানের পদ্ধতি এবং বিভিন্ন মাসআলায় তাঁর ফিকহী অভিমত আলোচনার প্রয়াস নেয়া হয়েছে। বর্ণনামূলক পদ্ধতিতে রচিত এ প্রবন্ধে তাঁর থেকে বর্ণিত ফিকহী বিধান সম্বলিত হাদীসসমূহের উল্লেখ ও তাঁর নিজস্ব অভিমত তুলে ধরা হয়েছে। প্রবন্ধটি থেকে ফিকহী বিধানের ব্যাপারে উম্মু সালামা রা.-এর গভীর পা-িত্য বিশেষত মহিলা ফিকহে তাঁর অবস্থান ফুটে ওঠেছে।